Free and immobilized laccases for in-situ and ex-situ polycyclic aromatic hydrocarbons bioremediation - Perini, Brayam Luiz Batista (2020)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2020.